Systemic Adverse Events Associated with Locally Administered Corticosteroids - Femke De Vleeschhauwer; Kristina Casteels; Ilse Hoffman; Marijke Proesmans; Anne Rochtus (MDPI AG, 2024)
Topical corticosteroids are a mainstay in the treatment of many pediatric disorders. While they have proven beneficial therapeutic effects and are generally considered safe, systemic adverse events may occur. This study presents four cases of children who experienced systemic adverse events after using inhaled and intranasal topical corticosteroids, as well as topical corticosteroids in other forms. A comprehensive literature review was performed to explore the existing evidence on this topic. The aim of this study is to raise awareness among healthcare providers about the possibility of systemic adverse events associated with the use of locally administered corticosteroids in pediatric patients. This information underscores the importance of careful monitoring, individualized treatment plans, and further research to better understand and mitigate the risks associated with corticosteroids, even those not given systemically.